Honduras : Second Reviews Under the Stand-by Arrangement and the Arrangement Under the Standby Credit Facility, Requests for Augmentation and Rephasing of Access, and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Honduras. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper presents Honduras' Second Reviews Under the Stand-By Arrangement and Arrangement Under the Stand-By Credit Facility, Requests for Augmentation and Rephasing of Access, and Modification of Performance Criteria. The coronavirus disease 2019 pandemic and external spillovers are expected to hit Honduras hard, and the augmentation of access will support the authorities' response to mitigate the impact. The completion of the reviews will help Honduras meet urgent balance of payments needs stemming from the pandemic, including increased health care and social spending. The authorities continue to take steps to improve the institutional framework in the electricity sector. Important measures have been incorporated into the program. These aim at improving governance and facilitating the unbundling of the national electricity company. Tariffs continue to reflect the cost of electricity provision while providing subsidies to the poor. The augmentation of access under the Stand-By Arrangement and the Arrangement under the Standby Credit Facility should help the authorities cover external financing needs to mitigate the impact of the pandemic.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet